Konsep dan Perkembangan Teori Maqasid - Agus Marimin (ITB AAS INDONESIA Surakarta, 2022)
Maqâshid al-Syarî'ah are the ultimate goals that must be realized with the application of syar'at or Islamic law. The application of syar'at in real life (world), is to create the benefit or goodness of creatures on earth, which then has an impact on benefit or goodness in the hereafter. Excavation of benefits by the mujtahids, can be done through various methods of ijtihad. Basically, these methods lead to an effort to find